I non eroi di Carlo Cassola - Armellin Secchi, Giovanna (Universidad de Costa Rica, 2015)
Carlo Cassola nació en Roma en 1907 y vivió en Toscana. Esta región se convirtió en el espacio donde se desarrollan sus novelas. Además, en sus trabajos se narra sobre personas comunes y sus problemas cotidianos, en un marco de problemas sociopolíticos. Carlo Cassola was born in Rome in 1907, and lived in Toscana. This region inspired him and not only he lived there, but also Toscana became the stage of his novels. Ordinary people and their daily problems are the aim, although sociopolitical problems are usually the frame of his literary works.